Cochlear implant indications: a review of third-party payers' policies for standard and expanded indications. (4th July 2021) - Moses, Lindsey E.; Friedmann, David R.
Abstract : As cochlear implant (CI) candidacy has expanded, commercial payers in the United States have varied in their adoption of new indications, potentially confusing providers' knowledge about appropriate patients for referral. We reviewed how third-party payers classify the medical necessity of cochlear implants for a variety of indications across the lifespan. We compared policies of the six largest commercial payers in our region, focusing on clinical scenarios for which many centers experience difficulty obtaining pre-authorization. These include: (1) CI in children under 12 months, (2) audiometric and speech perception criteria in children, (3) sequential bilateral CI, (4) electro-acoustic stimulation, (5) impending cochlear ossification, and (6) single-sided deafness (SSD). Of the more notable findings for the clinical scenarios half of commercial payers have a pediatric age requirement of greater than 12 months. Generally, audiologic and speech perception criteria are more stringent for children than adults across all policies. SSD is considered investigational by most policies. Third-party payers employ variable criteria regarding the medical necessity of CI, many of which are not contemporaneous with clinical knowledge and best practices. This may impact referral patterns among audiologists. More methodologically rigorous clinical trials may help shift such restrictive policies to benefit a greater number of patients.